Law N ° 28977 and its influence on the risk management of Rapid Delivery Shipments 2007-2010 - Rodriguez Alvarado, Piero Alonso (2018)
Objective: To determine if the Foreign Trade Facilita- tion Law - (Law No. 28977, 2007) that creates fast delivery shipments (EER) for goods entering the country, limits an appropriate risk management by the Air and Postal Customs during the 2007-2010 period. Method: This is a descrip- tive, causal, quantitative research, based on numerical evaluation and statistical analysis, the sample consisted of fifty (50) foreign trade user’s experts in the research mat- ter; the methods of Kendall's Tau_b and of Spearman were applied. Results: The hypothesis that posed a direct relationship between the variables was verified since the behavior of similarity that exists in the graphics obtained in the contrast of the variables, obtained a p calculated value (0,0005), which is below the level of significance of the 5%, The results show that (Law N ° 28977, 2007) is a limiting factor for adequate risk management of merchandise ente- ring the country as fast delivery shipments. Conclusion: An appropriate risk management must be carried out with the modifications of the current norms. Additionally, the computer systems used for cross-referencing information with the Regimen of fast shipment delivery module should be adequate every time officials make use of the online tools (invoices- fast delivery shipments (EER) guides).